Microstructure and strength of composite casting interface between Ti pretreated SiCf/SiC and Ni-based superalloy - LIN Guobiao; ZHU Fuhu; ZHAO Siwen (Cailiao gongcheng, 2024)
The integrated castings fabricated by SiCf/SiC composite and K403 Ni-based superalloy melt exhibited spontaneous fracture when cooled to room temperature. The integrated forming of SiCf/SiC and K403 Ni-based superalloy and their firmly bonded interface were successfully realized by pretreatment of SiCf/SiC surface using Ti powder embedded coating infiltration process at 1100 ℃ and ceramic mold precision casting with K403 superalloy melt under appropriate process. The results show that the Ti pretreatment layer has an average thickness of about 17 μm and microscopic structure including TiC, Ti3SiC2, Ti5Si3Cx and SiC phases owing to Ti permeation, diffusion and reaction to SiCf/SiC. After composite casting of the pretreated SiCf/SiC and high temperature nickel base metallic liquid, the pretreatment layer is evolved into the interface reaction layer with a thickness of about 120 μm and the typical microstructure composed of Ni2Si, C, Al4C3 and MC (M containing mainly Ti and a small amount of Cr, Mo, W).The existence of pretreatment layer alleviates the harmful graphitization reaction between Ni and SiC, and the thermal shock of the high temperature melt on SiCf/SiC during casting; the formed interface reaction layer reduces the interface thermal stress caused by the mismatch of thermal expansion coefficients. Consequently, the room temperature shear strength of the interface in the integrated casting of SiCf/SiC and K403 reaches 63.5 MPa.